Comparative Assessment of Widefield Fundus Autofluorescence Patterns in Retinoschisis and Retinal Detachment. (July 2020) - Cao, Jessica L.; Conti, Thais F.; Hom, Grant L.; Babiuch, Amy S.; Greenlee, Tyler; Ehlers, Justis P.; Rachitskaya, Aleksandra; Sharma, Sumit; Yuan, Alex; Kaiser, Peter K.; Singh, Rishi P.
Purpose: This article characterizes widefield fundus autofluorescence (WF-FAF) patterns in retinoschisis (RS), retinal detachment (RD), and combined retinoschisis-detachment (RS/RD), and to correlate them with spectral-domain optical coherence tomography (SD-OCT) findings. Methods: A retrospective case series of 13 eyes with senile RS, RD, or RS/RD is presented. One eye underwent imaging of 2 areas within the retina, resulting in 14 data points. Independent, masked graders classified pathology on SD-OCT as RS, RD, or RS/RD and graded WF-FAF images for either hypoautofluorescent areas or mixed autofluorescence (AF) (hyper-AF, iso-AF, hyper-AF with hypo-AF, hyper-AF with iso-AF, or hypo-AF with iso-AF). Results: There was no statistically significant correlation between the autofluorescence pattern and the type of retinal abnormality ( P = .74). Conclusions: High variability was found in the characterization of WF-FAF in patients with RS and RD. SD-OCT remains the criterion-standard imaging modality in distinguishing RS from RD in clinically ambiguous cases.